ANALISIS TINGKAT KETELITIAN METODE BISEKSI BERDASARKAN NILAI GALAT DALAM MENENTUKAN AKAR PERSAMAAN NONLINIER - Siti Khayroiyah; Jelita Aprillia; Risa Dwi Anggraini; Windi Sintia Pratiwi; Nur Amelia Kartika Nasution; Fildzah Nurkhaira Adli; Nora Anjana Sari Rangkuti; Najwa Azzahra Lubis; Nabila Azzahra; Ariansyah Putra Siregar (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study aims to analyze the accuracy level of the bisection method in determining the roots of nonlinear equations based on the error values obtained in each iteration. The background of this research is the difficulty of obtaining exact solutions for nonlinear equations, so numerical methods are requmetired as an alternative approach. The method used in this study is a descriptive quantitative approach by performing systematic calculations through an iterative process. The object of this research is a nonlinear function with an initial interval of , which satisfies the condition for the existence of a root, indicated by a sign change of the function at the interval boundaries. The solution process is carried out using the bisection method by repeatedly dividing the interval until an approximate value close to the actual root is obtained. In each iteration, the midpoint value and error value are calculated to measure the accuracy level of the method. The results show that the approximate root obtained is . The error value decreases consistently as the number of iterations increases, indicating that the bisection method has a stable convergence property.